Pemikiran Afzalur Rahman Tentang Tata Kelola Pertanahan dan Relevansinya di Indonesia - Abubakar Sidik (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2016)
In economic activity appeared the three actors in it; State, the private sector, and communities that each had different bargaining positions, such as access to capital and political access with respect to natural resources such as land that limited. Changes in economic perspective view toward the rapidly developing ground. Currently the ground further highlighted its function as capital assets and commodities, the mastery and utilization of land depended on market mechanisms. This meant that capitalist contributed to intervene the mastery and ownership of land. This affected concentrated on a handful of people who had big capital with more tendency to speculative rather than productive. Results of the research which was found that Rahman had a general idea that the fundamental principle of the whole body of norms or rules in economic activity was turn the attitude of altruism, namely the altruistic rather than personal interests. In particular, first; Rahman rationale was, as a basic theological importance of managing in the form of hard work to meet the livelihood so that they did not fail or lagging from others in the struggle for survival. Rahman explained that the emphasis on man's efforts to obtain a source of livelihood was one of the fundamental economic principles in Islam; if this principle ignored it will meet with failure causing poverty and starvation. Secondly, in terms of basic thoughts of Rahman on the corporate governance of the land of Islam over to an aspect of the economic approach based on the production of the agricultural sector, ranging from the certainty of land ownership which affected toward the result of increased production, land distribution, the production of the agricultural sector which emphasized the holding of insurance with the principles of